Does Good Knowledge On Dengue Correlates To The Practice Of Dengue Prevention? A Survey Among A Rural Community In Negeri Sembilan - Nuurain Amirah Mohd Razi; Nizam Baharom; Nadeeya Mohamad Nor; Mohd Dzulkhairi Mohd Rani; Akmal Aizat Rosman; Zairina A. Rahman (UPM PRESS, 2024)
Malaysian Journal of Medicine and Health Sciences Vol.15 Supp 6, October 2019 (eISSN 2636-9346) ABSTRACTS FOR THE 1ST INTERNATIONAL BORNEO HEALTHCARE AND PUBLIC HEALTH CONFERENCE AND 4TH BORNEO TROPICAL MEDICINE AND INFECTIOUS DISEASE CONGRESS New Frontiers in Health: Expecting the Unexpected